IMPLEMENTASI MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V SEKOLAH DASAR - Mesa, Ivoni; Siti Ni’matul Fitriyah; Muh. Fauzy Emqi; Moh. Farid Nurul Anwar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Critical thinking is an important skill that students must possess to face the challenges of 21st-century learning. The Problem Based Learning (PBL) model is one approach that can be used to develop critical thinking skills because it emphasizes active and contextual problem solving. This study aims to improve critical thinking skills after the implementation of the Problem Based Learning (PBL) model in each CAR cycle. This study uses the Classroom Action Research (CAR) method which is implemented in two cycles, where each cycle consists of planning, implementation, observation, and reflection stages. The research subjects were 29 students. Data collection techniques were carried out through observation, testing, and documentation. Data analysis was carried out qualitatively and quantitatively. The results of this study indicate that there was an increase in students' critical thinking skills in each cycle. In the pre-cycle stage, the percentage of student learning completion was 34.48%, then increased to 68% in cycle I, and increased again to 86% in cycle II. This increase indicates that the implementation of the Problem Based Learning model has a positive impact on student learning outcomes. Students' critical thinking skills improved because they were actively involved in the learning process through problem-solving activities, group discussions, and analysis of the given problems. Based on the research results and discussion, it can be concluded that the implementation of the Problem-Based Learning model was effective in improving the critical thinking skills of fifth-grade students at SDN Madyopuro 1.